VIRTUAL REALITY AS A REPRESENT OF SPATIAL PERCEPTION OF MAIN CHAPEL ROOM AT THE CHURCH OF LIGHT - Putro, Hendro Trieddiantoro (ARSITEKTURA, 2018)
The research focused on the Virtual Reality in order to represent spatial perception. The research object was a Virtual Reality simulation of Main Chapel at The Church of Light. There was 9 spatial perception category to describe Main Chapel at The Church of Light that founded from literature study. The research used a virtual reality simulation and a semantic differential questionnaire. There are 40 students joined the research. They divided into 2 groups of architectural background groups and non-architectural background groups. They join the virtual reality simulation then tested with a semantic differential questionnaire. The research concluded with the effectiveness of Virtual Reality. The spatial perception of the main chapel at The Church of Light can be represented using Virtual Reality simulation. According to 7 spatial perception category that is represented, Virtual Reality can be categorized as an effective medium to representing spatial perception. Moreover, analyze results to6 pairs word that relate to 2 perception category that not in accordance with the  literature study, specifically to the darkness and detail of the object. This could happen because of a lack of quality in Virtual Reality  simulation product. The lack that produced from the low contrast effect and unmatched material reflection or miss match with the real condition.